2019
DOI: 10.1093/ofid/ofz248
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Lactam/Beta-Lactamase Inhibitor Therapy for Potential AmpC-Producing Organisms: A Systematic Review and Meta-Analysis

Abstract: The optimal treatment for potential AmpC-producing Enterobacteriaceae, including Serratia, Providencia, Citrobacter, Enterobacter, and Morganella species, remains unknown. An updated systematic review and meta-analysis of studies comparing beta-lactam/beta-lactamase inhibitors with carbapenems in the treatment of bloodstream infections with these pathogens found no significant difference in 30-day mortality (OR, 1.13; 95% CI, 0.58 – 2.20).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
11
1
2
Order By: Relevance
“…Antimicrobial treatment of patients with SPICE-BSI remains challenging in clinical practice. Although carbapenems are the gold standard for treatment of severe infections, alternative carbapenem-sparing treatment options are needed [10][11][12]14] to prevent increases in carbapenem resistance [15]. Whereas most previous studies have assessed treatment outcomes by comparing 30-day mortality rates among different treatment regimens [10,11,16,17], this study focused on early treatment response on day 3 as the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobial treatment of patients with SPICE-BSI remains challenging in clinical practice. Although carbapenems are the gold standard for treatment of severe infections, alternative carbapenem-sparing treatment options are needed [10][11][12]14] to prevent increases in carbapenem resistance [15]. Whereas most previous studies have assessed treatment outcomes by comparing 30-day mortality rates among different treatment regimens [10,11,16,17], this study focused on early treatment response on day 3 as the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although carbapenems are the gold standard for treatment of severe infections, alternative carbapenem-sparing treatment options are needed [10][11][12]14] to prevent increases in carbapenem resistance [15]. Whereas most previous studies have assessed treatment outcomes by comparing 30-day mortality rates among different treatment regimens [10,11,16,17], this study focused on early treatment response on day 3 as the primary outcome. The main findings of our study were that early treatment response was significantly lower in the piperacillin/tazobactam group than in the carbapenem group (p = 0.006) despite similar disease severities (median SOFA score: 3.0 versus 4.5, p > 0.2) and that empiric piperacillin/tazobactam use (AOR 0.25, p < 0.001), baseline SOFA score (AOR 0.83, p < 0.001) and liver comorbidity (AOR 0.32, p = 0.018) were independently associated with early treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the use of piperacillin-tazobactam might be a promising alternative to carbapenems for the management of Enterobacteriaceae bloodstream infections, especially when MIC piperacillin-tazobactam is low (MIC ≤ 0.5/4 µgL) or the source of bloodstream infection is the genitourinary tract or abdomen [37]. Furthermore, some studies have also suggested that piperacillin-tazobactam may be a potential alternative to carbapenems in the treatment of AmpC-producing Enterobacteriaceae [41].However, further studies are essential to provide a more accurate and de nitive assessment of the effectiveness against beta lactambeta lactamase inhibitors versus carbapenems, especially since some studies still consider carbapenems to be superior to others regimes [37,41]. Furthermore, no studies have been conducted in this regard on pediatric LT until now.…”
Section: Discussionmentioning
confidence: 99%
“…Algunos β-lactámicos no carbapenems, como la cefepima o la piperacilinatazobactam, se consideran inductores débiles, por lo que pueden ser una alternativa en algunas circunstancias mediante el uso de dosis alta y perfusión extendida. 15 Se recomienda evitar el uso de piperacilina-tazobactam en infecciones con inóculo alto o con aislamientos con CMI de piperacilina-tazobactam > 8 mg/L, y de cefepima en aislamientos con CMI de cefepima > 1 mg/L. 16 La cefepima generalmente no se hidroliza por las AmpC, por lo que es una excelente opción.…”
Section: Tratamientounclassified